Pemberian Pupuk Hayati dengan Interval Waktu Aplikasi Berbeda terhadap Perkembangan Penyakit Rebah Semai dan Pertumbuhan Sawi (Brasica Rapa) di Pesemaian - Silvia Kilian; A. Marthin Kalay; Abraham Talahaturuson (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2022)
Seedling fall disease caused by the fungus Rhizoctonia solani is one of the limiting factors in the cultivation of mustard plants. This pathogen can attack plants in the nursery as well as after the plants in the field. The aim of this study was to determine the effect of using biological fertilizers Azoto-Trico and KIBPF with different application time intervals on the development of seedling fall disease and the growth of mustard in the nursery. The study used Azoto-Tricho and KIBPF biological fertilizers with application intervals of 2 days, 4 days and 6 days. The results showed that the application of biological fertilizers Azoto-Tricho and KIBPF with different application time intervals had an effect on controlling seedling fall disease and increasing plant height and plant fresh weight. The application of Azoto-Tricho biofertilizer and KIBPF if applied at intervals of 2 days or 4 days or 6 days had the same ability to control seedling fall disease and increase plant height and fresh weight of mustard plants in nurseries.